Multiscale design of cell-free biologically active architectural structures - Ho, G.; Kubušová, V.; Irabien, C.; Li, V.; Weinstein, A.; Chawla, Sh.; Yeung, D.; Mershin, A.; Zolotovsky, K.; Mogas-Soldevila, L. (Frontiers in Bioengineering and Biotechnology, 2023)
Cell-free protein expression systems are here combined with 3D-printed structures to study the challenges and opportunities as biofabrication enters the spaces of architecture and design. Harnessing large-scale additive manufacturing of biological materials, we examined the addition of cell-free protein expression systems (“TXTL” i.e. biological transcription-translation machinery without the use of living cells) to printed structures. This allowed us to consider programmable, living-like, responsive systems for product design and indoor architectural applications. This emergent, pluripotent technology offers exciting potential in support of health, resource optimization, and reduction of energy use in the built environment, setting a new path to interactivity with mechanical, optical, and (bio)chemical properties throughout structures. We propose a roadmap towards creating healthier, functional and more durable systems by deploying a multiscale platform containing biologically-active components encapsulated within biopolymer lattices operating at three design scales: (i) supporting cell-free protein expression in a biopolymer matrix (microscale), (ii) varying material properties of porosity and strength within two-dimensional lattices to support biological and structural functions (mesoscale), and (iii) obtaining folded indoor surfaces that are structurally sound at the meter scale and biologically active (we label that regime macroscale). We embedded commercially available cell-free protein expression systems within silk fibroin and sodium alginate biopolymer matrices and used green fluorescent protein as the reporter to confirm their compatibility. We demonstrate mechanical attachment of freeze-dried bioactive pellets into printed foldable fibrous biopolymer lattices showing the first steps towards modular multiscale fabrication of large structures with biologically active zones. Our results discuss challenges to experimental setup affecting expression levels and show the potential of robust cell-free protein-expressing biosites within custom-printed structures at scales relevant to everyday consumer products and human habitats.